BrUFO positively regulates the infection of Chinese cabbage by Plasmodiophora brassicae - Zhang, Bo; Feng, Hui; Ge, Wenjie; Wang, Xinlei; Zhang, Jing; Ji, Ruiqin (Frontiers in Plant Science, 2023)
Chinese cabbage is one of the most important vegetable crops in China. However, the clubroot disease caused by the infection of Plasmodiophora brassicae (P. brassicae) has seriously affected the yield and quality of Chinese cabbage. In our previous study, the Bra039878 protein was found to be significantly upregulated in diseased roots of Chinese cabbage after inoculation with P. brassicae. Herein, for the purpose of exploring its function, we cloned and analyzed the full-length cDNA sequence of BrUFO, which showed BrUFO was high homology with Arabidopsis UNUSUAL FLORAL ORGANS (UFO), so it was named BrUFO. Quantitative real-time polymerase chain reactions (qRT-PCR) and in situ hybridization analysis showed that expression of BrUFO in the resistant plants was lower than that in susceptible plants. Subcellular localization analysis showed that BrUFO was expressed in the nucleus. Virus-induced gene silencing (VIGS) analysis showed that silencing of BrUFO reduced the incidence of clubroot disease. Six proteins interacting with BrUFO were screened by Y2H assay. Two of them (Bra038955, a B-cell receptor-associated 31-like protein and Bra021273, a GDSL-motif esterase/acyltransferase/lipase Enzyme) were confirmed to strongly interact with BrUFO. Therefore, BrUFO may play a key role in regulating disease resistance to clubroot by interacting with Bra038955 and Bra021273.